2017
DOI: 10.1155/2017/1803934
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Fractal Search Algorithm for Template Matching with Lateral Inhibition

Abstract: Template matching is a basic and crucial process for image processing. In this paper, a hybrid method of stochastic fractal search (SFS) and lateral inhibition (LI) is proposed to solve complicated template matching problems. The proposed template matching technique is called LI-SFS. SFS is a new metaheuristic algorithm inspired by random fractals. Furthermore, lateral inhibition mechanism has been verified to have good effects on image edge extraction and image enhancement. In this work, lateral inhibition is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…For example, the problem of measuring the similarity between two overlapping sets of images is known as template matching. The work in [35] used stochastic fractal search to solve this problem, comparing the experimental results with algorithms, such as artificial bee colony and imperialist competitive algorithm, among others. The results showed that the algorithm obtained a better performance in contrast to other works present in the literature.…”
Section: State Of the Artmentioning
confidence: 99%
“…For example, the problem of measuring the similarity between two overlapping sets of images is known as template matching. The work in [35] used stochastic fractal search to solve this problem, comparing the experimental results with algorithms, such as artificial bee colony and imperialist competitive algorithm, among others. The results showed that the algorithm obtained a better performance in contrast to other works present in the literature.…”
Section: State Of the Artmentioning
confidence: 99%
“…SFS strategy has been successfully tested in various fields of science in the mono-objective context, such as:template matching (Luo et al 2017), mathematical functions (Zuo et al 2017), 3D protein structure prediction (Zhou et al 2018), distribution systems (Nguyen et al 2018), combined heat and power economic dispatch problem (Alomoush, 2019), economic load dispatch (Pham et al 2019), solar photovoltaic parameter estimation (Chen et al 2020), among other studies.…”
Section: Multi-objective Optimization Stochastic Fractal Searchmentioning
confidence: 99%
“…One of these algorithms is the stochastic fractal search (SFS) algorithm developed by Salimi [24]. The SFS algorithm has been applied to many optimization problems and has yielded successful results [25][26][27][28][29][30][31][32][33][34][35]. These algorithms can be used to solve complex computational optimization problems, however, fast convergence along with accuracy is not guaranteed.…”
Section: Introductionmentioning
confidence: 99%